Perbaikan Postur Kerja menggunakan Metode REBA pada Area Assembly Engine - Haris David Sitorus; Hendi Herlambang; Yudi Prastyo (TIN: Terapan Informatika Nusantara, 2026)
This study aims to analyze ergonomic risks and propose improvements to working posture using the Rapid Entire Body Assessment (REBA) method in the Assembly Engine area. The research was conducted through direct observation, documentation of operators’ working postures, interviews, and distribution of Nordic Body Map (NBM) questionnaires. The results showed that several work activities had moderate to high ergonomic risk levels caused by bending postures, repetitive movements, and non-ergonomic component handling activities. The most common complaints experienced by operators were related to the neck, back, waist, and wrists. Based on the REBA analysis results, several improvements are required, including workstation layout adjustments, use of assistive devices, improvement of working methods, and implementation of ergonomic training. The proposed improvements are expected to reduce the risk of Musculoskeletal Disorders (MSDs), improve operator comfort, and support productivity and occupational safety sustainably within the production environment.